Joseph P. Schaufenbuel letter to Thomas H. Kent regarding bird sightings, March 3, 1980 - Schaufenbuel, Joseph P.et al (1980)
Field notes contributed by Joseph P. Schaufenbuel in a letter to Thomas H. Kent, March 3, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1979-1980. Epson - sheet feed/flatbed